Corrosive Injury of the Upper Gastrointestinal Tract: A Review - Rathnaswami Arunachalam; Ashwin Rammohan (Archives of Clinical Gastroenterology - Peertechz Publications, 2016)
Ingestion of a corrosive substance can produce severe injury to the gastrointestinal tract and can even result in death. The degree and extent of damage depends on several factors like the type of substance, the morphologic form of the agent, the quantity, and the intent. In the acute stage, perforation and necrosis may occur. Long-term complications include stricture formation in the esophagus, antral stenosis and the development of esophageal carcinoma. Endoscopy should be attempted and can be safely performed in most cases to assess the extent of damage. Procedure related perforation is rare. Stricture formation is more common in patients with second and third degree burns. This review summarizes our current knowledge and evidence based management of this unique but not uncommon pathology of the upper gastrointestinal tract.